187 Utilizing Working Groups to Provide Hands-On Learning Opportunities for Experienced Beef Cattle Producers. (28th November 2020) - Vining, Timothy P; Jacobs, Joshua L; Marks, Marty L; Thompson, Gerald L; Mullenix, Mary K
Abstract: The Systems 360° Working Group program was created for experienced beef cattle producers who desired to learn more about timely topics related to beef cattle production than could be covered in a single night meeting. To aid in developing these working groups, the Alabama Extension Animal Science and Forages Team developed curriculum regarding grazing management, watering systems, marketing, handling facilities, and animal management. Regional animal science and forages agents then coordinated planned visits to producer farms and Auburn University research centers that highlighted specific management practices surrounding these topics, and facilitated group discussion at those sites to encourage peer-to-peer learning experiences. A working group consisted of beef cattle producers (n = 10–25 participants per group) sharing a common interest in learning more in-depth about strategies to improve their respective operations. Four working groups were organized in different regions of Alabama and met five times throughout 2018–2019. The closing survey (n = 50 responses) for the working groups indicated that 100% of participants felt this program met expectations, and given the opportunity they would join another working group. Overall, 94% of respondents indicated that they planned to adopt one of more of the management practices discussed in the group in the next 12 months. Top practices that producers planned to implement included improved winter grazing strategies, rotational stocking, water resource management and testing, and facilities design/animal handling. Producers indicated that they learned the most from farm-visits and speakers/discussion leaders as part of the program. Participants reported that knowledge gained from this program could potentially lead to a total farm economic impact averaging 6, 095 per operation. These data indicate that Systems Working Groups are an effective means to disseminate knowledge, engage producers in peer-based learning opportunities and improve herd profitability among experienced beef cattle producers.